2007
DOI: 10.1103/physrevb.75.184306
|View full text |Cite
|
Sign up to set email alerts
|

Decay of a nonlinear impurity in a structured continuum from a nonlinear Fano-Anderson model

Abstract: The decay dynamics of a nonlinear impurity mode embedded in a linear structured continuum is theoretically investigated in the framework of a nonlinear Fano-Anderson model. A gradient flow dynamics for the survival probability is derived in the Van Hove ͑ 2 t͒ limit by a multiple-scale asymptotic analysis, and the role of nonlinearity on the decay law is discussed. In particular, it is shown that the existence of bound states embedded in the continuum acts as transient trapping states which slow down the decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…6,7 The model attracted interest long time ago because of analytical treatment and its generality. 2,6,7,9 The main result is that the transmission coefficient of a single waveguide mode scattering from Kerr off-channel features was shown to exhibit bistability properties arising from a nonlinearity of the offchannel site. In Refs.…”
Section: Tight-binding Model Of the Nonlinear Fabry-perot Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…6,7 The model attracted interest long time ago because of analytical treatment and its generality. 2,6,7,9 The main result is that the transmission coefficient of a single waveguide mode scattering from Kerr off-channel features was shown to exhibit bistability properties arising from a nonlinearity of the offchannel site. In Refs.…”
Section: Tight-binding Model Of the Nonlinear Fabry-perot Systemmentioning
confidence: 99%
“…The system attracts interest over decade because of analytical treatment and its generality. [2][3][4][5][6][7][8][9][10][11][12] On the other hand, the system can be realized in the twodimensional photonic crystals ͑PhC͒.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, considerable research interest has been generated on decay dynamics of straight waveguides embedded into a linear structured continuum of waveguides. The decay dynamics was theoretically investigated [18] for a nonlinear impurity mode embedded in a linear structured continuum in the framework of a nonlinear Fano-Anderson model. It was shown that the existence of bound states embedded in the continuum acts as transient trapping states which slow down the decay.…”
Section: Introductionmentioning
confidence: 99%